Bacterial fight-and-flight responses enhance virulence in a polymicrobial infection - Stacy, Apollo (National Academy of Sciences, 2014)
The oral pathogen Aggregatibacter actinomycetemcomitans (Aa) resides in infection sites with many microbes, including commensal streptococci such as Streptococcus gordonii (Sg). During infection, Sg promotes the virulence of Aa by producing its preferred carbon source, l-lactate, a phenomenon referred to as cross-feeding. However, as with many streptococci, Sg also produces high levels of the antimicrobial hydrogen peroxide (H(2)O(2)), leading to the question of how Aa deals with this potent antimicrobial during coinfection. Here, we show that Aa possesses two complementary responses to H(2)O(2): a detoxification or fight response mediated by catalase (KatA) and a dispersion or flight response mediated by Dispersin B (DspB), an enzyme that dissolves Aa biofilms. Using a murine abscess infection model, we show that both of these responses are required for Sg to promote Aa virulence. Although the role of KatA is to detoxify H(2)O(2) during coinfection, 3D spatial analysis of mixed infections revealed that DspB is required for Aa to spatially organize itself at an optimal distance (>4 µm) from Sg, which we propose allows cross-feeding but reduces exposure to inhibitory levels of H(2)O(2). In addition, these behaviors benefit not only Aa but also Sg, suggesting that fight and flight stimulate the fitness of the community. These results reveal that an antimicrobial produced by a human commensal bacterium enhances the virulence of a pathogenic bacterium by modulating its spatial location in the infection site.